Microbial Community Analyses of the Deteriorated Storeroom Objects in the Tianjin Museum Using Culture-Independent and Culture-Dependent Approaches - Liu, Zijun; Zhang, Yanhong; Zhang, Fengyu; Hu, Cuiting; Liu, Genliang; Pan, Jiao (Frontiers in Microbiology, 2018)
In the storeroom C7 of the Tianjin Musuem, one wooden desk and two leather luggages dated back to Qing dynasty (1644-1912 AD) presented viable microbial contamination. The aim of the present study was to investigate microbial communities responsible for the biodeterioration of storeroom objects using a combination of culture-independent and culture-dependent methods as well microscopic techniques. Scanning electron microscopy (SEM) revealed that the microflora on three storeroom objects were characterized by a marked presence of Eurotium halophilicum. Real-time quantitative polymerase chain reaction (qPCR) analysis proved that fungi were the main causative agents behind the biodeterioration in this case. Fungal internal transcribed spacer (ITS) amplicon sequencing documented the presence of two main fungi — Eurotium halophilicum and Aspergillus penicillioides. Molecular identification of fungal strains isolated from the surfaces and the air of the storeroom were most closely related to Chaetomium, Aspergillus, Penicillium, and Fusarium, showing discrepancies in fungal taxa compared to ITS amplicon sequencing. The most isolated bacterial phylum was Firmicutes, mostly Bacillus members. In addition, four biocide products — Preventol® D 7, P 91, 20 N and Euxyl® K 100 were selected to test their capability against fungal strains isolated from the surfaces. According to the susceptibility assay, Preventol® D 7 based on isothiazolinones was the most effective against fungal isolates. Findings from this study provided a knowledge about storeroom fungi, and exemplify a type of preliminary test that may be conducted before planning any biocide treatment, which may be useful to mitigate the fungal deterioration for further conservation of the museum.